Instrumen Distribusi dalam Ekonomi Islam - Saiful Anwar (Institut Agama Islam Agus Salim Metro Lampung, 2020)
Abstract Distribution in the Islamic concept does not only prioritize economic aspects where size is based on the amount of property owned, but also discusses how the use of human potential can be distributed, in the form of appreciation for the right to life in life. Then the distribution is expected to overcome the problem of income distribution between various classes in society. Therefore in Islam Allah SWT implies one form of social virtue, like zakat. If this is used as the concept of income distribution, the economic system will run smoothly and the community will prosper. Gap and hunger will easily be eliminated due to the prevalence of the distribution system. And in Islamic economics a person's wealth does not make the cause of others experiencing economic difficulties, both production and consumption. Therefore Islam provides clear boundaries in living this life, including regulating matters regarding distribution. The whole is to regulate so that there is no social inequality between one party and another party and have an impact on actions or counterproductive. Therefore Islam stipulates the existence of distribution instruments, including the principle of cooperation between mudharabah and musyarakah, the existence of zakat, infaq, alms and endowments as well as other assets or income owned. Keyword: Distribution, Islamic Economics, Economic System